176k views
2 votes
How do you solve -2(5+6x)+16=-90

User Barn
by
7.3k points

2 Answers

3 votes
first, distribute negative two to 5 and 6x. you should then have -10 • (-12x) + 16 =-90
after you get that follow order of operations. 120x + 16 = -90. next subtract 16 from both sides of the equation. 120x = -106.

x= -53/60
How do you solve -2(5+6x)+16=-90-example-1
User Cedric Petetin
by
7.1k points
4 votes
Hi there,

-2(5 + 6x) + 16 = -90
-10 - 12x + 16 = -90
6 - 12x = -90
- 12x = -90 - 6
-12x = -96

Hence, X = 8

Hope this helps :)
User Tkyass
by
7.4k points